ASUHAN KEPERAWATAN KELUARGA DENGAN PENERAPAN EDUKASI DALAM MENURUNKAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI DESA MONGOLATO - Andi Nur Aina Sudriman; Rona Febriyona; Nur Fadhilah Saleh (Pusat Riset dan Inovasi Nasional, 2023)
Introduction ; Hypertension is a multifactorial disease that arises due to the interaction of various factors. High blood pressure that is not controlled properly can cause high blood pressure permanently, hypertension is a serious and dangerous disease because if hypertension is not controlled it can cause dangerous complications such as coronary heart disease, visual disturbances and kidney disorders. the leading cause of death in the world. Method ; Research design This study uses a case study research design (Nursing Care) the research design uses a qualitative approach with pre-experiments. Results ; Hypertension status before being given the application of education to Mrs. Y 160/100 mmHg, to Mrs. Y 180/100 mmHg and to Mrs. K.K 180/100 mmHg, hypertension status in the three patients was seen to have changed or decreased after being given the application of health education, this was seen in the first day, namely on Mrs. Y 150/100 mmHg, on Mrs. Y 160/100 mmHg and on Mrs. K.K 160/100 mmHg. On the second day after being given health education, Mrs. Y 150/100 mmHg, Mrs M.Y 150/100 mmHg and Mrs, K.K 160/100 mmHg. Whereas on the third day, Mrs A.Y 140/100 mmHg, Mrs M.Y 140/100 mmHg and Mrs, K.K 140/100 mmHg. Conclusion ; The results of the overall evaluation after nursing actions were carried out, namely observing that the patient's blood pressure decreased, the patient could feel pain independently, as well as health education for patients and their families. Families can care for patients suffering from hypertension.